(untitled) (Swiss Medical Weekly, 2015)
Multiple sclerosis (MS) is the most common inflammatory demyelinating disorder of the central nervous system (CNS). Over the past 10 years there has been a heated debate as to whether MS pathogenesis commences in the CNS or whether it is actually primarily a disease of the immune system. The combined clinical data, therapy responses, pathology, animal models and genetic studies now provide overwhelming support for the concept that MS is a disease of the immune system and that the CNS is only the unfortunate target of a misguided immune attack. Immune cells communicate through the use of cytokines and these proteins can orchestrate the most complex behaviour in immune cells. We propose that MS is a disease where immune communication is derailed, which makes MS very amenable to immunotherapy and in particular makes cytokines an attractive target to repair this miscommunication disorder.